2020
DOI: 10.1186/s12961-020-00603-y
|View full text |Cite
|
Sign up to set email alerts
|

Communities of practice in Alberta Health Services: advancing a learning organisation

Abstract: Background: In 2009, Alberta Health Services (AHS) became Canada's first and largest fully integrated healthcare system, involving the amalgamation of nine regional health authorities and three provincial services. Within AHS, communities of practice (CoPs) meet regularly to learn from one another and to find ways to improve service quality. This qualitative study examined CoPs as an applied practice of a learning organisation along with their potential influence in a healthcare system by exploring the perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 32 publications
(37 reference statements)
0
19
0
6
Order By: Relevance
“…17 The Unit Lead CoPs were chosen as critical pathways for information sharing by connecting Unit Leads working in geographic isolation with modest resource requirements. 2 The Unit Lead CoPs varied in frequency from weekly to once per month providing additional learning opportunities for members to explore ways to address local…”
Section: Unit Lead Community Of Practicementioning
confidence: 99%
See 2 more Smart Citations
“…17 The Unit Lead CoPs were chosen as critical pathways for information sharing by connecting Unit Leads working in geographic isolation with modest resource requirements. 2 The Unit Lead CoPs varied in frequency from weekly to once per month providing additional learning opportunities for members to explore ways to address local…”
Section: Unit Lead Community Of Practicementioning
confidence: 99%
“…AHS is the largest provincial health authority in Canada and serves 4.3 million residents with more than 850 hospitals, community clinics, and continuing care facilities. 2 AHS, similar to many healthcare organizations, is challenged with achieving the organizational goal of introducing evidence-based initiatives to create efficiencies in providing quality care and sustaining such changes. In order to implement the changes necessary across such a vast geographical area and adapt to subtle and overt differences across the zones and sectors, a purposeful implementation strategy was needed such as using a peer champion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] They enable the diverse wealth of knowledge embedded in people, local conditions and special circumstances to ow from practice domain groups to program and service areas, and into the larger system where it can effect organizational change. [5] In 1991 Lave and Wenger [6] developed the concept of the CoP. They suggested that learning takes place in social relationships rather than through the simple acquisition of knowledge.…”
Section: Communities Of Practice (Cops)mentioning
confidence: 99%
“…13 Although studies evaluating the impact of COPs on population health remain scarce, at the process level, COPs have been found to enable organisational change through the flow of knowledge from practice to programme and service areas, and into larger systems. 14 Promising interventions with COPs include a facilitator to enhance interaction, use of information technology to enable communication and provision of organisational infrastructures to promote uptake of new knowledge. 15 COPs for specific health programmes have employed different social media platforms and pathways such as podcasts and virtual meetings for continuous engagement and knowledge exchange with target groups.…”
Section: Introduction Overview Of Social Innovation In Healthmentioning
confidence: 99%